Open e v+ a 2007 : A sense of place - Ottmann, Klaus; O'Reilly, Paul M; Limerick City Gallery of Art (Oysterhaven : Gandon Editions, 2007)
Martinez Celaya, Enrique ; Corcoran, Patrick ; Corcoran, Shelley ; Dunne, David ; Earley, Melissa ; Foley, Barry ; Glavin, Eric ; Gunning, Tony ; Hauft, Amy ; Holmes, Ashley ; et al.
Limerick City Gallery of Art, Limerick, 30 March - 24 June 2007
kunstcatalogus